2018
DOI: 10.17569/tojqi.397652
|View full text |Cite
|
Sign up to set email alerts
|

E-Portfolio Implementation Experiences of Prospective Primary School Teachers

Abstract: In the information society, as in all other institutions the functions of educational institutions have changed by the phenomenon of globalization, the rapid spread of knowledge and reaching broad masses, the necessity of coexistence of differentiated cultures, and the development of science and technology. Portfolios help students to assess themselves and improve their ability to express themselves and allow observation of the development that takes place over a specified period due to the collection of work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, it creates a sense of professional identity in preparing for professional practice. Anagun, Atalay and Kandemir (2018) have found that the e-portfolio is useful for pre-service teachers in preparing lesson plans, gaining practical experience, increasing their awareness and providing personal and professional development. Sidebotham et al (2018) have revealed that e-portfolios also provide an appropriate framework and real opportunity for pre-service teachers to identify and demonstrate their level of preparation for professional practice, to identify ongoing learning needs and to develop strategies for achieving them.…”
Section: Introductionmentioning
confidence: 99%
“…However, it creates a sense of professional identity in preparing for professional practice. Anagun, Atalay and Kandemir (2018) have found that the e-portfolio is useful for pre-service teachers in preparing lesson plans, gaining practical experience, increasing their awareness and providing personal and professional development. Sidebotham et al (2018) have revealed that e-portfolios also provide an appropriate framework and real opportunity for pre-service teachers to identify and demonstrate their level of preparation for professional practice, to identify ongoing learning needs and to develop strategies for achieving them.…”
Section: Introductionmentioning
confidence: 99%